Propagation Of Barn Owls, Tyto Alba Javanica For Controlling Of Rat Populations In Urban Area Of Minden, Penang. - Saufi, Mohamad Safwan Mohd (2020)
In this study, 25 barn owls, Tyto alba javanica were translocated from their original habitat and were introduced in urban area of Minden, Penang Island since 2016 in order to establish their population and to serve as a natural enemy against rat pests. Prior to release the barn owls into urban area, food preferences and feeding behaviour of T. alba javanica in captivity were investigated. The Mann-Whitney analysis test showed that there was no significant difference (p>0.05) between different 2 species of rats (Rattus tiomanicus and Rattus norvegicus) as the barn owls preferable diets. However, the barn owls showed their preference towards small active, small inactive (<50g) medium active followed by medium inactive (80-120g) meanwhile larger preys were less preferable (180-220g). Next, molecular sexing method of T. alba javanica was carried out to compare ten morphological traits to determine the barn owls sexes; body mass, spotting patterns and plumage colour, tarsus length, talons, wingspan, tail, facial disc, primary and secondary remiges, presence of brood patches and culment length. This study showed that sex identification using morphological trait had 83.3% and 78.57% accuracy for both female and male respectively. Furthermore, the results indicated that the presence of brooding patch were the most second most accurate and reliable to determine the barn owls sexes (accuracy of 100% and 75% for male and female respectively).